EFFECT OF OXYGEN AVAILABILITY ON β-IONONE FORMATION AS A DEGRADATION PROCESS OF CAROTENOIDS FROM CRUDE PALM OIL BY THERMAL PROCESS - Daimon Syukri; Adlis Santoni; Rini; Ismed; Jaswandi; Ira Desri; Rahmi; Zaibunnisa Abdul; Haiyee; Annisa Rahmi Z.J; Poppy Amelia; Rahadian Zainul (The Iraqi Journal of Agricultural science)
This study aimed to observe the effect of oxygen levels during the carotenoid degradation process to produce β-ionone, several parameters have been pointed, including carotenoid levels in CPO before and after the degradation process using a spectrophotometer, the color of the CPO solution before and after degradation using the color flex hunter lab and the β-ionone levels resulting from the degradation of Carotenoids by gas chromatography using a mass spectrometry detector. As the result, it can be stated that the presence of oxygen has influenced the degradation of carotenoids in CPO. The greater the amount of oxygen, the more carotenoids are degraded. The most excellent degradation process was found to be 80%. However, β-ionone was only detected in the air flow treatment of 20 L/h with a value of 0.44 mg/L. The results of this research have shown that the amount of oxygen dramatically influences the formation of β-ionone when the carotenoid degradation process is carried out under hot conditions. This information can be used to develop β-ionone formation technology for future industrial-scale application.